Educating Students with Refugee and Asylum Seeker Experiences A Commitment to Humanity - Sellars, Maura (Verlag Barbara Budrich, 2020)
This book discusses the educational systems into which students with refugee backgrounds are placed when relocated into many of their new homelands. It discusses the current climate of neo liberalism which pervades schooling in many western countries and the subsequent impact on curriculum focus and teaching strategies. It proposes ways in which these students, who are currently the most vulnerable students in school, can be educated with policies and perspectives which respect the diversity and uniqueness that characterises the world today as the result of the global unrest and subsequent diaspora. The impact of power, politics, people and pedagogies on the prospects of these is investigated and a model for holistic education, which includes the wisdom and care of pedagogical love is discussed as way in which a more human and compassionate approach to education for these and all students of difference can be integrated into school communities despite neo liberal imperatives in education. Research indicates that schools which are spaces of safety and belonging, through leadership of care and empathy, can provide successful educational opportunities for students who have asylum seeker and refugee backgrounds and experiences.